서울의 비휴일과 휴일 간 미세먼지 농도 차이의 시·공간적 변동 - 김종원(Jong-Won Kim); 한범순(Beom-Soon Han); 백종진(Jong-Jin Baik) (한국대기환경학회지(국문), 2020)
The temporal and spatial variations of workday-holiday PM10 concentration differences in Seoul were investigated using observation data collected at 25 urban air quality monitoring stations from 2001 to 2017. The 17-year average workdayholiday PM10 concentration difference is 9% of the average PM10 concentration (54.1 μg m-3). The annual average PM10 concentration exhibited a decreasing trend. The annual average workday-holiday PM10 concentration difference was large before 2005, and the annual average PM10 concentrations in workdays and holidays were not significantly different after 2005. When Saturday was included in public holidays or yellow dust events appeared more frequently in holidays, the annual average workday-holiday PM10 concentration difference generally decreased. The seasonal average workday-holiday PM10 concentration differences in spring, summer, fall, and winter are 3%, 8%, 13%, and 11% of the average PM10 concentrations, respectively. In spring, yellow dust events reduced the workday-holiday PM10 concentration difference significantly. The hourly average workday-holiday PM10 concentration difference increased in the morning rush hour, up to 12% of the daily average PM10 concentration. This increase was related to the difference in PM10 emission between workdays and holidays which was larger in the morning rush hour. The spatial variability of the average PM10 concentrations at the 25 stations is 3%, and that of the average workday-holiday PM10 concentration differences is 2%. The spatial variability of the average PM10 concentrations decreased in holidays due to the reduced PM10 emission in commercial, business, and industrial areas. In those areas, the workday-holiday PM10 concentration differences are as large as 12% of the average PM10 concentration. Also, the annual average PM10 concentrations in southwest and north areas of Seoul tended to increase and decrease compared to the rest of Seoul, respectively. KCI Citation Count: 0